1996
DOI: 10.1093/jn/126.12.3046
|View full text |Cite
|
Sign up to set email alerts
|

An Extract of Soy Flour Influences Serum Cholesterol and Thyroid Hormones in Rats and Hamsters

Abstract: The effects of an ethanol-acetone extract from soy flour on serum lipids and thyroid hormones were studied in rats and hamsters. In Study 1, male Sprague-Dawley rats were fed diets containing protein from ethanol-acetone extracted isolated soy protein (ISP-), nonextracted ISP (ISP), casein (casein-), or casein to which 0.36 mg ethanol-acetone extract/g protein was added (casein+). Rats fed either ISP-containing diet had lower serum total cholesterol concentrations compared with those fed either casein diet (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 21 publications
6
66
1
1
Order By: Relevance
“…The experimental diets contained ∼37% of energy as fat, 25% casein, and 0.1% cholesterol (8). Rice flour was used as a carbohydrate source to prevent "wet tail" disease, a chronic diarrhea that may kill hamsters (1).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental diets contained ∼37% of energy as fat, 25% casein, and 0.1% cholesterol (8). Rice flour was used as a carbohydrate source to prevent "wet tail" disease, a chronic diarrhea that may kill hamsters (1).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, consumption of vegetable protein is being increased every day. Soybean is a widely used vegetable seed [8]. In this study, diets containing soybean meal showed a significant decrease in blood cholesterol levels than the control group.…”
Section: Discussionmentioning
confidence: 56%
“…Methionine and low ratio of lysine to arginine, a parameter that decreases cholesterol, are constituent components of soybean protein [7]. Also some nonprotein compounds of soybean are reported to have beneficial effects on improvement of plasma cholesterol [8]. In addition, soybean contains the highest level of isoflavones among vegetable proteins.…”
mentioning
confidence: 99%
“…It is well known that mammalian oestrogens have a significant impact on serum lipids, promoting decreases in LDL and increases in HDL cholesterol. Evidence for an effect of isoflavones on serum cholesterol concentrations has been demonstrated in rats, hamsters, nonhuman primates and humans (Cassidy et al, 1995;Pelletier et al, 1995;Anthony et al, 1996;Balmir et al, 1996;Clarkson et al, 1998). The three primate studies reported by Anthony et al (1994Anthony et al ( , 1995aAnthony et al ( , 1995b demonstrated that soy protein rich in isoflavones favourably affected serum lipids, and that soy protein from which the oestrogens had been extracted had a minimal effect.…”
Section: Cholesterol-lowering Properties Of Soy Potential Cholesterolmentioning
confidence: 99%